2019
DOI: 10.1080/15548627.2019.1644075
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light on autophagy coordinating with cell wall integrity signaling to govern pathogenicity of Magnaporthe oryzae

Abstract: Cells are faced with various stresses during their growth and development, and autophagy is a degradative process in which cells can break down their own components to recycle macromolecules and provide energy under these stresses. For pathogenic fungi that utilize cell wall as the first barrier against external stress, the cell wall integrity (CWI) pathway also provides an essential role in responding to these stresses. However, the specific connection between autophagy and CWI remains elusive in either the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 80 publications
0
109
0
Order By: Relevance
“…Autophagy is known to be related to several stress responses (Yin et al 2019). However, it remains unclear whether UvATG8 regulates stress responses of U. virens.…”
Section: Uvatg8 Is Involved In Various Stress Responsesmentioning
confidence: 99%
“…Autophagy is known to be related to several stress responses (Yin et al 2019). However, it remains unclear whether UvATG8 regulates stress responses of U. virens.…”
Section: Uvatg8 Is Involved In Various Stress Responsesmentioning
confidence: 99%
“…Our previous study revealed that M. oryzae suffers additional ER stress when it switches from vegetative growth to asexual reproduction (Tang et al, 2015). Recently, Yin et al reported the presence of ER stress during M. oryzae infection (Yin et al, 2020). These data indicated that M. oryzae had to adapt to ER stress changes during fungal development.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, Yin et al reported that DTT imposed ER stress induces autophagy in M. oryzae (Yin et al, 2020).…”
Section: Mohrd1 and Moder1 Contribute To Lipid Metabolism And Autophagymentioning
confidence: 99%
“…We previously found that MoMkk1 also mediates crosstalk between the CWI pathway and other pathways, including the unfolded protein response (UPR) pathway, the high osmolality glycerol (HOG) MAPK pathway, and autophagy [ 10 ]. We demonstrated that the autophagy-related kinase MoAtg1 phosphorylates MoMkk1 under ER stress [ 16 ]. By identifying the cell cycle-related kinase MoSep1 that phosphorylates MoMkk1 to enhance the CWI activity, we revealed the complex and multitude of signaling pathway crosstalk surrounding CWI.…”
Section: Discussionmentioning
confidence: 99%
“…oryzae , the MAP kinase pathway is composed of MoMck1 (the Bck1 homolog), MoMkk1 (the Mkk1/2 homolog), and MoMps1 (the Mpk1/Slt2 homolog) that play an essential role in aerial hyphae morphogenesis, appressorium formation, and pathogenicity [ 10 , 14 – 15 ]. In addition, recent studies have found that other kinases, such as autophagy-related MoAtg1, could also phosphorylate MoMkk1 in response to the endoplasmic reticulum (ER) stress [ 16 ]. This study suggested the importance and the multitude of regulatory mechanisms by CWI signaling.…”
Section: Introductionmentioning
confidence: 99%